Estimating the impact of quality adjustment on consumer price inflation - Jan-Oliver Menz; Elisabeth Wieland; Jens Mehrhoff (Deutsche Bundesbank, 2022)
How much does quality adjustment matter in measuring consumer price inflation? To address this question, we use different sources of micro and macro price data for Germany and the euro area. For Germany, we find that quality adjustment applies to a large range of goods and services but, on average, price adjustments due to quality changes reduce headline inflation only by 0.06 percentage points, which is balanced out by an increase due to quantity adjustment (e.g. a smaller package size) of the same amount. For the euro area, we assess the impact of heterogeneous quality adjustment methods by deriving the distribution of member states' cumulative inflation rates for typical quality-adjusted products. Our macro-based estimate makes up to ± 0.2 percentage points for headline HICP inflation and ranges between ± 0.1 and 0.3 percentage points for core inflation, when controlling for income differentials between member states. Finally, we illustrate the role of heterogeneous quality adjustment methods in the euro area based on micro price data for washing machines. We show that the price development of this product would have been lower by about 3.5 percentage points during the first years of the euro area and by about half a percentage point during recent years, if prices in the member states had been quality-adjusted in exactly the same way.
Keywords: E31; C43; 330; inflation measurement; quality adjustment; inflation differentials; micro price data